PENGARUH BRAND AWARENESS, BRAND IMAGE, DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN SEPEDA LISTRIK DI JEPARA - Nirmala Auliya Firdaus; Nurul Huda (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the influence of brand awareness, brand image, and influencer marketing on electric bicycle purchasing decisions in Jepara.             The research method used a quantitative approach with purposive sampling techniques involving 100 respondents who are electric bicycle users in the Jepara area. The data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method through SmartPLS 4 software.             The results showed that brand awareness, brand image, and influencer marketing had a positive and significant effect on purchasing decisions with a p-value < 0.05. Influencer marketing has the most dominant influence, followed by brand awareness and brand image. The research model is able to explain 65% of the variation in electric bicycle purchase decisions. This study provides a theoretical contribution in strengthening consumer behavior theory and a practical contribution for business actors in developing marketing strategies based on brand strength and collaboration with relevant influencers.